2017
DOI: 10.1161/atvbaha.117.309777
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Suppresses Coronary Hyperconstricting Responses After Drug-Eluting Stent Implantation in Pigs In Vivo Through the Kidney–Brain–Heart Axis

Abstract: These results provide the first evidence that RDN ameliorates drug-eluting stent-induced coronary hyperconstricting responses in pigs in vivo through the kidney-brain-heart axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The anti-angiogenic strategy for vasa vasorum may cause intramural hemorrhage as a consequence of increased vascular permeability [ 26 ]. We previously demonstrated that catheter-based renal sympathetic denervation is effective to suppress DES-induced coronary hyperconstricting responses via the kidney-brain-heart-axis in pigs in vivo [ 6 ]. We also developed a balloon-catheter based technique to deliver adenovirus-mediated gene transfer of C-type natriuretic peptide gene in pigs in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-angiogenic strategy for vasa vasorum may cause intramural hemorrhage as a consequence of increased vascular permeability [ 26 ]. We previously demonstrated that catheter-based renal sympathetic denervation is effective to suppress DES-induced coronary hyperconstricting responses via the kidney-brain-heart-axis in pigs in vivo [ 6 ]. We also developed a balloon-catheter based technique to deliver adenovirus-mediated gene transfer of C-type natriuretic peptide gene in pigs in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“… 45 48 A recent study using pigs discovered that this approach reduced blood pressure and improved cardiovascular functions through its influence on kidney-brain-heart axis with profound changes of plasma renin activity, implicating the involvement of the renal renin-angiotensin system regulation in the process. 49 …”
Section: Reninmentioning
confidence: 99%
“…Catheter-based renal denervation also significantly upregulates the expression of alpha-2 adrenergic receptor-binding sites in the nucleus tractus solitarius, and attenuates adventitial VV enhancement associated with a decrease in SNF. [33]…”
Section: Future Perspectivesmentioning
confidence: 99%